PRENATAL YOGA DI PMB E KP. LAMPEGAN KELURAHAN CIMUNCANG KABUPATEN GARUT - Lina Humaeroh; Esa Risi Suazini; Fitri Hanriyani (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Pregnancy is an important event in the life of a woman and her family in general. Discomfort arises as a result there are some changes in pregnant women. The midwifery care provided toreduce the physical discomfort of pregnant women is oriented towards preventive care that iseasy for mothers to do. Yoga is an activity or exercise that can be done by everyone, includingpregnant women. Yoga in pregnancy or often referred to as prenatal yoga can reduce the physicaldiscomfort of pregnant women and can make the mother's mood better. This service activity aimsto remind pregnant women of the importance of light exercise/activity during pregnancy. Themethod of activity was carried out in the form of direct prenatal yoga practice with 9 pregnant women participating. Knowledge of pregnant women increases after the activity andthe perceived complaints are reduced.